Development of Education in Emerging India - Bahadur, Vir; Kumar, Vikas (Integrated Journal for Research in Arts and Humanities, 2024)
Education isn't confined to a specific period; it's an ongoing journey that lasts a lifetime. Throughout our lives, we continually acquire knowledge, as the saying goes, "we learn something new every day." Adult education plays a vital role in enhancing literacy rates within societies and countries. By improving basic literacy skills, adults unlock their full potential, both personally and professionally. This newfound confidence encourages them to explore beyond their comfort zones and engage with the world around them. Learning isn't bound by age; it's a continuous process that knows no limits. Education shouldn't be restricted solely to children and teenagers; instead, it should extend seamlessly into adulthood and beyond. There's immense value in lifelong learning, as the scope of knowledge is vast and ever-expanding. Adult education offers mature learners the chance to broaden their understanding, acquire fresh skills, and attain valuable qualifications. In essence, there's no expiration date on learning – it's a journey that enriches lives at any stage.